Pendampingan SMK Pusat Keunggulan Dengan Pola Focus Group Discussion (FGD) di SMK Negeri 1 Kota Jambi - Sastya Hendri Wibowo; Diana (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2023)
Focus Group Discussion (FGD) is one of the agendas or patterns of assistance contained in the 2023 SMK Center of Excellence assistance, namely discussing with the school in achieving the desired target by the objectives of the Center of Excellence Vocational Program prepared in each school, This discussion involves the Principal, Vice Principal, Head of Department or Competence, productive teachers and other parties involved in the implementation of the SMK Center of Excellence Program. The material presented at the Focus Group Discussion (FGD) was 6 (six) meetings in the form of visitations every week, namely the fulfillment of 8 (eight) national education standards, the preparation of the need assessment of world of work partners, the implementation of vocational performance assessments, Development of data-based school resources, Development of industrial learning (teaching factory), Preparation of development plans for SMK Center of Excellence, Use of technology platforms in learning or education management Development of special job fairs and graduate tracking systems.